Sustaining separatist/terrorist/liberation movements in the 21st century : who does the financing? - Chigora, P. (International Conference on Public Administration and Development Alternatives, 2018)
The 21st century has seen the growth of insurgency, separatist, terrorist organisations and liberation movements, across the world, particularly in Africa and the Middle East, adding to the old ones that have spurned for decades in Central America and South Eastern Asia. These have threatened the consolidation of democracy and improvement of good governance. Despite their most unwelcome contribution to democratic governance and conflict zones through death, injuries and psychological trauma as well increasing vulnerability and fragility of entities they have continued to emerge and proving to be able to sustain their activities some of which have lasted for more than two or more decades. In order for these movements to sustain their activities they require heavy funding for project formulation and implementation given their organisational aims and objectives. Therefore, the purpose of this paper is to analyse the sources of funding behind these movements and organisations which have contributed to the instability of states not only in Africa but other developing countries. The paper will proffer some solutions to this ever persistent problem on human life. Keywords: Developing countries, Funding, Liberation movement, Organisations Separatist, Terrorist
Article published in: The 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Developing countries; Funding; Liberation movement; Organisations Separatist; Terrorist; Anti-imperialist movements; Civil rights movements; National liberation movements -- Africa